Measuring Expertise Learning Rates for Nonrepetitive Project Work (American Journal of Management, 2022)
Research on learning has largely centered around workers repeatedly performing a specific set of tasks. However, in service functions like management consulting, jobs are seldom repetitive. Nevertheless, expertise is acquired with practice. This paper proposes a model to quantify learning when a consistent methodology is applied to a wide variety of projects, and introduces an associated ‘expertise learning rate’. The model is illustrated using panel data tracking 56 newly trained process improvement project leaders completing 233 projects over five years. Applications where trained personnel must work on nonrepetitive jobs or projects are common in services, e.g., insurance claims settlement, cost estimation in construction, and tax return preparation in accounting.
Keywords: management; learning rates; process improvement projects; management consulting